Pendampingan Literasi Gizi dan Kepatuhan Minum Obat Pasien TB Anak pada Agrocommunity - Ningtyias, Farida Wahyu; Nafikadini, Iken; Prasetyowati, Irma (UNEJ e-Proceeding, 2023)
Background: Tuberculosis (TB) is the 10th most deadly disease globally. Indonesia has the third-largest TB incidence in the world. TB in children is often overlooked due to difficult diagnosis and medication adherence. The role of parents with good knowledge is very important to support the prevention and treatment of TB in children. Method: Knowledge improvement was achieved through literacy about nutrition and TB using Flipchart and Flashcard media "The ABCs of Children with TB" to target guardians of pediatric TB patients and cadres. The activity was carried out at the Sukorambi Health Center Hall on August 12, 2022, using a pre-posttest. Results: The activity went well, attended by 22 guardians of pediatric TB patients and cadres. There was a 3% increase in knowledge. The media was felt to help the education process and was easily understood by the target. Conclusion: Flipchart and Flashcard media "The ABCs of Children with TB" can be used as a tool for cadres when conducting educational activities in the community related to the topic of prevention and treatment of TB in children. Keywords: childhood, flashcard, flipchart, nutritional education, tuberculosis.